2014
DOI: 10.1111/ppe.12165
|View full text |Cite
|
Sign up to set email alerts
|

Does Late Childbearing Increase the Risk for Behavioural Problems in Children? A Longitudinal Cohort Study

Abstract: This study showed no evidence that late fatherhood is associated with adverse behavioural outcomes in offspring. Increasing maternal age was found to be a protective factor for child behaviour morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 36 publications
2
21
0
6
Order By: Relevance
“…A study using data from a prospective birth cohort in Western Australia recruited from 1989 to 1991 examined the relationship between maternal age and behavior outcomes in childhood and adolescence (49). Using parentreported Child Behavior Checklist data collected at ages 2, 5, 8, 10, 14, and 17, the authors found significant linear relationships between maternal age and child behavior outcomes.…”
Section: Older Maternal Age and Behavioral Outcomes In Offspringmentioning
confidence: 98%
“…A study using data from a prospective birth cohort in Western Australia recruited from 1989 to 1991 examined the relationship between maternal age and behavior outcomes in childhood and adolescence (49). Using parentreported Child Behavior Checklist data collected at ages 2, 5, 8, 10, 14, and 17, the authors found significant linear relationships between maternal age and child behavior outcomes.…”
Section: Older Maternal Age and Behavioral Outcomes In Offspringmentioning
confidence: 98%
“…Nonetheless, evidence regarding the relationship between maternal age and child depression remains inconclusive. Some researchers have found that children of younger mothers are at higher risk for internalizing problems (Fergusson & Woodward, 1999;Tearne et al, 2015). However, others have not found a relationship between maternal age and child mood disorders (Buizer-Voskamp et al, 2011;McGrath et al, 2014), and some have found that children who were born to older mothers had statistically higher levels of depression, anxiety, and stress in early adulthood than did those born to younger mothers (Tearne et al, 2016).…”
Section: Family and Mother Risk Factors (Microsystem Level)mentioning
confidence: 99%
“…Como se evidencia en la Tabla, 16 estudios indagaron los factores protectores y de riesgo del TC junto a los síntomas asociados. 14 estudios identificaron factores protectores (Bernat et al, 2012;Betancourt et al, 2012;Burt, Wildey, y Klump, 2015;Colder et al, 2013;Chinchilla y Kosson, 2015;Dunsmore, Booker, y Ollendick, 2013;Fanti, Kimonis, Hadjicharalambous, y Steinberg, 2016;Flouri, Mavroveli, y Panourgia, 2013;Ibabe, Jaureguizar, y Bentler, 2013;Nilsson et al, 2016;Schlauch, Levitt, Connell, y Kaufman, 2013;Taubner, White, Zimmermann, Fonagy, y Nolte, 2013;Tearne et al, 2015) Estudio transversal N = 183 jóvenes desplazados (10-17 años). Se examinaron las relaciones entre el apoyo social y la conexión con la familia, y el entorno social en relación con la internalización de los problemas.…”
Section: Trastornos De La Conducta (Tc)unclassified
“…factores de riesgo (Bernat et al, 2012;Carballo et al, 2013;Colder et al, 2013;Chinchilla y Kosson, 2015;Dunsmore et al, 2013;Fanti et al, 2016;Taubner et al, 2013;Taubner, Zimmermann, Ramberg, y Schroder, 2016;Tearne et al, 2015). Factores protectores.…”
Section: Trastornos De La Conducta (Tc)unclassified